(untitled) (Patan Pragya, 2022)
This article analyses the constitutional and legal provisions for school education and particularly Compulsory and Free Education Act, 2075 of Nepal. These provisions are oriented toward creating an environment where all citizens can get basic education so as to enhance equal and just Society. Compulsory and Free Education Act, 2075 is enacted to implement the constitutionally Assured fundamental right to education, and provision of free and compulsory school education without evidence-based analysis, planning and budgeting. The provisions of Compulsory and Free Education Act, 2075,in essence, are closed to the imposed social order from the top envisioned by Durkheim, influence and control of the powerful section of the society by Weber and inequality in the society due to unequal access to education by the classical Marxists.